The Role Of Adaptation In Increasing The Resilience Of The Kapuas River Tourism Community To Flooding In Pontianak - Andrasmoro, Dony -; Eviliyanto, Eviliyanto (EL-JUGHRAFIYAH, 2024)
ABSTRACK. Pontianak City, located on the banks of the Kapuas River, is the cultural and economic center of West Kalimantan and often faces the threat of recurrent flooding, disrupting the local community and economy. This research aims to assess community resilience in the Kapuas River Watershed (DAS) tourist area and identify effective adaptation strategies to flooding. Using quantitative methods and a descriptive spatial approach, the research focuses on the spatial distribution of physical and human phenomena and disaster response interactions between elements in the Kapuas watershed area. Data were collected through observations, interviews, and questionnaires distributed in several neighborhoods along the riverbanks. The results showed that the level of community resilience varies from moderate to high, depending on the components of resilience measured using a Likert scale, with the identification of the percentage of two aspects, namely Knowledge and Education Insight Capability is highest in Benua Melayu Darat Village with a value of 2.82 High categories, influenced by the high level of socialization and the use of FloodGuard technology facilities as an implementation of flood warnings. and Disaster Preparedness and Response is highest in Kelurahan Banjar Serasan with a value of 3.38. The High category is influenced by the level of knowledge and high human resources which also affects the preparedness of information but is constrained in handling efforts due to the influence of community mobilization of high community work, medium category in Benua Melayu Darat Village 2.3. The results showed strategies to increase community awareness and training through campaigns and training; building disaster-resistant infrastructure and evacuation facilities in neighborhoods along the Kapuas watershed. These measures have been able to sustain the community and increase the tourism attractiveness of the area through disaster preparedness.